Factors influencing farmers' participation in water management: a community development perspective - Sheikh, Muhammad Javed; Redzuan, Ma'rof; Abu Samah, Asnarulkhadi; Ahmad, Nobaya (International Organization Of Scientific Research, 2014)
Participation is believed to a systematic involvement of the significant number of people, in diverse activities to manage their own problems, carrying the concept of togetherness, which enhance the advantages. It always oscillates and depends on the background in which it occurs. Farmers' participation is critical to improve on-farm water management and crop productivity. The study was conducted to identify the factors involved in the fluctuation of participation. This paper reports the results, in which, farmer participation through planning, implementation, monitoring and evaluation of water-user associations were measured, and it was linked to various socioeconomic, demographic, and farm and irrigation characteristics. Multiple linear regression analysis reveals that the participation was positively influenced by age, education, residential locality, house type, lack of on-farm facilities, underground water use for irrigation purpose and location of watercourses on the canal network. However, residential locality and on-farm facilities have significantly negative relationships with the dependent variable in Sindh province of Pakistan.